2021
DOI: 10.3390/ijerph18105190
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Autism Spectrum Disorder and Pesticides: A Systematic Review of Human and Preclinical Models

Abstract: Autism spectrum disorder (ASD) is a complex set of neurodevelopmental pathologies characterized by impoverished social and communicative abilities and stereotyped behaviors. Although its genetic basis is unquestionable, the involvement of environmental factors such as exposure to pesticides has also been proposed. Despite the systematic analyses of this relationship in humans, there are no specific reviews including both human and preclinical models. The present systematic review summarizes, analyzes, and disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 109 publications
1
15
0
Order By: Relevance
“…The results of this review, relating to the maternal exposure to organophosphate in pregnancy or in the first years of a child's life and the risk of ASD onset, confirm the findings presented in a recent systematic review of human and preclinical models, which suggested that the gestational exposure to certain organophosphate agents could be linked to the clinical signs of ASD [18].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The results of this review, relating to the maternal exposure to organophosphate in pregnancy or in the first years of a child's life and the risk of ASD onset, confirm the findings presented in a recent systematic review of human and preclinical models, which suggested that the gestational exposure to certain organophosphate agents could be linked to the clinical signs of ASD [18].…”
Section: Discussionsupporting
confidence: 83%
“…The number of articles included in our review is small because we have specifically chosen to consider only the cohort and case-control studies involving humans and those which take into account the diagnoses of ASD in children based on the most recent diagnostic tools: DSM IV and V (Diagnostic and Statistical Manual of Mental Disorders, fourth edition and Diagnostic and Statistical Manual of Mental Disorders). On the contrary, other reviews that included a higher number of papers also considered in vitro and animal studies [18]. Increasing the number of studies included in a future meta-analysis could help to improve the statistical power and highlight the possible associations between the onset of ASD and the exposure to atmospheric pollutants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is commonly found in the food chain, soil, cigarette smoke, and manufactured products 73 . Research on pesticide exposure during childhood, specifically glyphosate 76, 77 , chlorpyrifos 77 , diazinon 77 , and the development of ASD continues to emerge 78-80 . Potential routes of pesticide exposure in children include food contaminated with pesticides (ingestion), in utero or through breastmilk, and household exposures via dermal contact 81, 82 .…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal exposure to mixtures of neurotoxic pesticides is prevalent worldwide and has the potential to disrupt and irreversibly alter neurologic development [ 1 - 3 ]. In 2017, approximately 8.8 billion pounds of pesticides were used worldwide [ 4 ].…”
Section: Introductionmentioning
confidence: 99%